Digital Library Universitas Muhammadiyah Gorontalo - Antupetu, Rastin; Abas, Mohamad Ilyas; Lasarudin, Alter; Lamusu, Rizal (Universitas Muhammadiyah Gorontalo, 2024)
This research was conducted at the Library of Universitas Muhammadiyah Gorontalo. The aim is to design a web-based library information system with a digital concept (Digital Library). The design of the Digital Library information system of Universitas Muhammadiyah Gorontalo, with a system design model using the prototyping model, provides a forum for students and lecturers, especially those on the campus of Universitas Muhammadiyah Gorontalo to publish research results in the form of theses, journals, and theses into this digital library system. With this digital library it will facilitate access for prospective graduates, both the academic community and academics outside the campus, who will take literature as a reference for the final report or thesis. Provide convenience in disseminating useful information or knowledge and help students conduct research.